Unraveling the Smart Charging Technologies, Energy Sources, and Regulatory Standards for EVs - Ansif Arooj; Qasim Zeeshan Ahmed; Muhammad Shoaib Farooq; Tariq Umer; Nauman Aslam; Temitope Alade (IEEE Access, 2025)
Electric vehicles (EVs) are anticipated to be pivotal contributors to the global energy transformation in the automobile industry, ignited by their rapid proliferation. However, the widespread integration of EVs requires rigorous research and synthesis in charging solutions and EV supply equipment to meet the expected performance and improve ancillary services. Analysing the current landscape of EV charging technologies, it is essential to accelerate EV adoption by incorporating advanced control strategies that mitigate negative impacts and improve charging efficiency. Thus, this study presents a meticulous review that culminates in a curated anthology of 81 pivotal articles, with a predominant emphasis on charging EVs and associated technologies. The findings reveal extensive potential in this domain with our rigorous scrutiny of studies uniquely integrating all critical EV charging technologies, including their taxonomy, on-board and off-board charging infrastructures, and the global standards, and future research directions. The revelations of the study elucidate the prevailing paradigms within the EV research nexus, charting a course for future scholarly pursuits and practical applications.